The life and work of Auleshi Sherpa Buddhist artist and adept - Ngawang Tengyé 1931-2022; Downs, Hugh R.; Kapstein, Matthew T. 1949- (Vajra Publications, 2024)
"The Sherpa Buddhist monk Ngawang Lekshé (1913-1983), familiarly known as Auleshi-a name that might be approximated as "Uncle Benedict" in English-occupies a unique place in the history of Buddhism in twentieth- century Nepal. At once an accomplished artist and a yogi living always in retreat, he eschewed the trappings of a "Buddhist master" but taught instead through his art and, above all, his personal example. In this, he embodied the ideal of transmitting the Dharma without teaching a word. As we honor the hundred-and-tenth anniversary of his birth, and fortieth since his death, with those who knew him now few, it seems appropriate to make available to all what may be recalled of his life and work. Hugh, who studied painting with Auleshi in the 1970s, gathered most of the texts and images on which this book is based, adding, too, a personal memoir. Matthew, who during the same period was studying Tibetan Buddhist philosophy with another Sherpa luminary, the late Serlo Khenpo Sangyé Tendzin (1924-1991), frequently met with Auleshi and so joined Hugh to prepare the materials he had collected for publication. The centerpiece of the work is Auleshi's biography, written by his nephew Ngawang Tengyé (1931-2022) of Kurseong, West Bengal, and presented here in English translation for the first time. We are indebted to the author's son, Jigme Losel Lama Sherpa, for making all versions of his father's text available to us, patiently responding to our queries, and enthusiastically encouraging this effort to commemorate his great-uncle Auleshi. We join him and his family in sorrow at Ngawang Tengyé's recent passing, before this work, alas, could see the light. We hope that its publication will be received as a worthy gesture of homage, both to the author and to his subject."
Literaturverzeichnis: Seite 145-151
Keywords: Ngawang Lekshé / 1913-1983; Buddhists / Nepal / Biography; Sherpa (Nepalese people) / Religion; Biografie